Pengaruh Tingkat Kemiskinan Dan Pengangguran Terhadap Indeks Pembangunan Manusia Di Provinsi Lampung - Anggy Dwi Safitri; Elsa Putri Vrasetya; Misfi Laili Rohmi (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
The Human Development Index (HDI) is the level of population welfare with indicators including, Education, Health and Income. This research aims to examine the influence of poverty and unemployment levels on the human development index in Lampung Province for 2014-2023. The research methods sourced from the Central Statistics Agency of Lampung Province with multiple regression analysis using Statistics Product for Service Solutions (SPSS) software. The results show that poverty has a significant effect on HDI while unemployment does not have a significant effect on HDI.